Cinnamon & Clove Café - Dzulkifli, Tarmizi; Ali, Muhammad Fikry; Kassim, Mohd Khairul Nizam; Haron, Hasrizal; Wan Musa, Wan Jeffry (Bachelor of Information Science (HONS.) Records Management, 2000)
Cinnamon & Clove Café, a new sidewalk café established as a partnership business. The venture capitalizes on the modern urban lifestyle where people prefer eating out and demand fast service and food due to their time-consuming, rushing routines. The café's name, Cinnamon & Clove Café, was chosen by the partners as these spices are commonly used in bakery and pastry making. The business is funded by five partners, each contributing RM 30,000 in capital, supplemented by a RM 150,000 loan secured from Bumiputra Commerce to cover all expenses. Despite existing competition in the café industry, the partners are motivated to continuously innovate new concepts and services to attract customers and elevate the business. The café is scheduled to begin operation on January 1, 2002, as stipulated in the partnership agreement.